Cool Japan's Role As A Japanese Public Diplomacy Strategy Through The Asia Kakehashi Project In Indonesia - Ayu Aruni; Triesanto Romulo Simanjuntak; Putri Herginasari (Eduvest - Journal of Universal Studies, 2022)
After World War II, Japan had a bad image in the international community. The Japanese government then tried to rise by using its public diplomacy strategy through educational instruments, namely the student exchange program initiated by Japanese Prime Minister Shizo Abe at the 23rd International Conference on The Future of Asia which aims to improve image, spread values and culture, and increase influence. Japan in the Asian region, including in Indonesia. To achieve this national interest, Japan uses its soft power element, namely Japanese popular culture through Cool Japan to attract foreign people to visit Japan, especially Asian people including Indonesia. The influence of Cool Japan has succeeded in improving the image of Japan as a country that is known to preserve and spread its uniqueness and positive values in its culture. This study uses qualitative research methods by conducting data/information searches that rely on humans and print media as research instruments. So in this study, we will discuss Cool Japan as one of Japan's public diplomacy activities to attract foreign people to visit Japan through the Asia Kakehashi Project student exchange program. Indonesia is one of the Asian countries appointed to send participants to take part in the Asia Kakehashi Project in Japan to participate in improving relations between the two countries by participating in a series of program activities by spreading values, understanding, experiences and positive opinions about what they get while in Japan.